Strategi Manajemen Resiko dalam Upaya Mengatasi Pembiayaan Murabahah Bermasalah pada PT.BPRS Puduarta Insani Cabang Uinsu - Tuti Damayanti Marbun; Nurul Jannah (STEI Kanjeng Sepuh Gresik Jawa Timur, 2022)
Since the establishment of banking with the sharia concept in 1998 until now, the market share of Islamic banking has only reached approximately 5%, while Islamic banking has become superior with a variety of very varied products. One of the advantages of Islamic banking lies in the profit-sharing system, so it is not wrong for people to call Islamic banks as profit-sharing banks, but in reality, financing in Islamic banking is not dominated by mudharabah financing with the concept of profit-sharing, but is more dominated by murabaha financing. Murabahah financing has always been a priority compared to other Islamic banking products. This can be seen from data from the Financial Services Authority (OJK) regarding the development of murabahah financing which tends to increase every month. This study uses a descriptive qualitative research approach that collects data through interviews and observations, and uses primary and secondary data sources. As well as using data analysis techniques and appropriate data collection techniques. The results of this study are that there are two factors, namely internal factors and external factors. The meaning of these two factors is that internal factors are caused by the lack of care by officers in analyzing financing customers, because they only use the principle of trust which is often misused by naughty customers, while external factors are caused by by intentional factors and unintentional factors. Based on the results of the research analysis and discussion that have been described, it can be concluded: At PT. BPRS Puduarta Insani itself has several handlings in problem financing, namely by billing according to the existing SOPs by providing SP 1,2 and 3, by persuasive (family) methods, then by reschduling, the last by way of selling guarantees but nothing has reached the stage sales guarantee.